Dynamic Modeling and Analysis of Demagnetizing Rotor of Permanent Magnet Synchronous Motor. (13th May 2021) - Zhou, Bifeng; Tang, Guoning; Luo, Yiping
Abstract : This study performs a dynamic modeling and analysis of the axial uniform demagnetization rotor of a motor to investigate the demagnetization peculiar for permanent magnet synchronous motor (PMSM). First, the air-gap change in the motor is analyzed by constructing a dual coordinate system of stator and rotor, and the unbalanced magnetic pull (UMP) model under uniform demagnetization and eccentricity is constructed. Second, combined with the UMP and the self-gravity, a dynamic model of the rotor under a uniform demagnetization and eccentricity is established. Lastly, the accuracy of the mathematical model of UMP under uniform demagnetization and eccentricity is confirmed by the mutual corroboration of Maxwell simulation and MATLAB calculation; and based on the dynamics model, the dynamic characteristics of the rotor system under different degrees of uniform demagnetization are studied. This study provides a theoretical basis for the accurate demagnetization fault diagnosis and vibration control of PMSMs in the future.